Frequência do gênero dos pacientes com hanseníase em relação à baciloscopia nos municípios do Estado do Espírito Santo - Maciel, Leonardo Bezerra (2013)
Background: Leprosy prevails as a public health problem in ten countries around the world, however, its control stops into complex cultural, social and biological questions. The frequency of the disease is apparently equal in both genders; however, there is a slight predominance of multibacillary forms in males, which could be explained by behavioral factors, or save some relation to biological factors. Objective: Evaluate the correlation of bacilloscopy with gender of leprosy patients in Espiríto Santo state (Brazil), in the period from 2001 to 2011. Patients and methods: Observational, descriptive and retrospective study of leprosy patients, notified at the Health Secretary of Espiríto Santo State. With these data we constructed a spreadsheet in SPSS Statistics 17.0 for statistical analysis. Results: From the 16030 leprosy cases reported was found that the majority were males (53%) had less than eight years of schooling (76%), they were concentrated in the north-central region of Espiríto Santo state (94%), predominated paucibacillary forms, however, multibacillary forms were most frequent among males (66%), with prevalence of positive bacilloscopy (72%) and neural involvement (62%). Conclusion: Men were the main responsible for the transmission and perpetuation of this endemic disease in the State of Espiríto Santo. Being men increased 2.54 times the risk of patients being multibacillary and increased 3.22 times the risk of patients presenting positive bacilloscopy.